2020
DOI: 10.1177/2055207620929785
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of the portrayal of childhood speech and language disorders in YouTube videos

Abstract: Purpose This study examined meta-data, source, type of informational content, understandability, and actionability of YouTube content related to speech and/or language disorders. Method The 100 most widely viewed videos related to children with speech and/or language disorders were obtained. Meta-data and sources of each upload were identified. Type of informational content within the videos was analyzed. The Patient Education Material Assessment Tool for Audiovisual Materials was used to assess understandabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…It employed more prescriptive search terms, since the broader search terms used in other studies may not have provided a representative sample of individual user needs. 11 Although Bozkurt and Aras reported on videos that included topics related to feeding, speech, and hearing, they did not specifically search nor detail the videos in these practice areas. Korkmaz and Buyuk did not search or report on feeding, speech, or hearing videos, though they did note that the most viewed video was about newborn feeding difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…It employed more prescriptive search terms, since the broader search terms used in other studies may not have provided a representative sample of individual user needs. 11 Although Bozkurt and Aras reported on videos that included topics related to feeding, speech, and hearing, they did not specifically search nor detail the videos in these practice areas. Korkmaz and Buyuk did not search or report on feeding, speech, or hearing videos, though they did note that the most viewed video was about newborn feeding difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Following previous studies on YouTube videos, 9 , 17 the validated Patient Education Materials Assessment Tool for Audiovisual Materials (PEMAT A/V) 18 was used to evaluate the understandability and actionability of the YouTube videos. There were 17 evaluation items that assessed the content, word choice and style, organization, layout and design, use of visual aids, and actionability.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that YouTube videos were frequently watched by adults with health problems 5 but generally had subpar quality and actionability. 6 11 Previous studies have evaluated the YouTube videos of dental radiography targeted for the professionals, such as radiographic procedures and radiographic anatomy. 12 14 However, it was of paramount importance to evaluate the videos dealing with the safety issue of dental x-rays targeted at the public.…”
Section: Introductionmentioning
confidence: 99%
“…The number of views of the videos and by whom they are uploaded is among the basic criteria for evaluating the quality. 9 Kollia et al 10 conducted a study on autism spectrum disorder and reported that the most viewed videos were uploaded and provided by non-professionals (e.g., personal videos and television program videos). However, experts have doubts about the reliability of such videos in terms of answering people's questions.…”
Section: Introductionmentioning
confidence: 99%